2023
DOI: 10.3390/diagnostics13243603
|View full text |Cite
|
Sign up to set email alerts
|

Arterial Stiffness as a Surrogate Marker of Cardiovascular Disease and Atherosclerosis in Patients with Vasculitides: A Literature Review

Konstantinos Triantafyllias,
Leif-Erik Thiele,
Anna Mandel
et al.

Abstract: Vasculitis, a group of systemic inflammatory diseases that affect the cardiovascular (CV) system, presents with a variety of clinical manifestations that depend on the size of the affected blood vessels. While some types of vasculitis reveal distinct symptoms, others are characterized by more diffuse and nonspecific presentations that can result in delayed diagnosis and treatment initiation. Interestingly, patients with vasculitides share a significant comorbidity: an elevated CV risk, contributing to increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 91 publications
0
0
0
Order By: Relevance
“…It has been recognized as a marker of vascular aging and has been found elevated in early stages of CVD development or in high-risk patients (e.g., diabetes) [4]. Thereby, scientific societies (the European Society of Cardiology and the European Society of Hypertension) recommend measuring of PWV as a screening test in the general population or as a surrogate index of CVDs, advocating its routine clinical application in cardiology daily practice [5][6][7]. In the context of SLE, characterized by higher CV risk, a recent meta-analysis of nine studies found significantly higher PWV in SLE patients compared to controls [8].…”
Section: Introductionmentioning
confidence: 99%
“…It has been recognized as a marker of vascular aging and has been found elevated in early stages of CVD development or in high-risk patients (e.g., diabetes) [4]. Thereby, scientific societies (the European Society of Cardiology and the European Society of Hypertension) recommend measuring of PWV as a screening test in the general population or as a surrogate index of CVDs, advocating its routine clinical application in cardiology daily practice [5][6][7]. In the context of SLE, characterized by higher CV risk, a recent meta-analysis of nine studies found significantly higher PWV in SLE patients compared to controls [8].…”
Section: Introductionmentioning
confidence: 99%